JAK/STAT signaling in stem cells and regeneration: from Drosophila to vertebrates - Herrera, Salvador C.; Bach, Erika A. (Development (Cambridge), 2019)
The JAK/STAT pathway is a conserved metazoan signaling system that transduces cues from extracellular cytokines into transcriptional changes in the nucleus. JAK/STAT signaling is best known for its roles in immunity. However, recent work has demonstrated that it also regulates critical homeostatic processes in germline and somatic stem cells, as well as regenerative processes in several tissues, including the gonad, intestine and appendages. Here, we provide an overview of JAK/STAT signaling in stem cells and regeneration, focusing on Drosophila and highlighting JAK/STAT pathway functions in proliferation, survival and cell competition that are conserved between Drosophila and vertebrates.